Respuesta :

f(x) = {(8, 3), (4, 1), (0, -1), (-4, -3)}
f(x) = ¹/₂x - 1

           f(x) = ¹/₂x - 1
              y = ¹/₂x - 1
              x = ¹/₂y - 1
           + 1         + 1
        x + 1 = ¹/₂y
    2(x + 1) = 2(¹/₂y)
2(x) + 2(1) = y
       2x + 2 = y
       2x + 2 = f⁻¹(x)
       2x + 2 = g(x)

g(x) = {(3, 8), (1, 4), (-1, 0), (-3, -4)}
g(x) = 2x + 2
Ver imagen Panoyin

The inverse g(x) of the relation f(x) is given by:

g(x) =  {(3, 8), (1, 4), (-1, 0), (–3, -4)}

How to find the inverse of the given relation?

For a relation:

f(x) = y.

We define the inverse g(x) as the relation such that:

g(y) = x.

This means that if (x₀, y₀) is a point on f(x), then (y₀, x₀) is a point on the inverse.

So, if:

f(x) =  {(8, 3), (4, 1), (0, –1), (–4, –3)}

We will have that the inverse is:

g(x) =  {(3, 8), (1, 4), (-1, 0), (–3, -4)}

If you want to learn more about inverses:

https://brainly.com/question/14391067

#SPJ2